Feasibility study of three-dimensional printing knee model using the ultra-low-dose CT scan for preoperative planning and simulated surgery - Meng Zhang; Ming Lei; Jie Zhang; Hongyi Li; Fenghuan Lin; Yanxia Chen; Jun Chen; Mengqiang Xiao (Insights into Imaging, 2022)
Abstract Objective To explore the feasibility of the three-dimensional printing (3DP) knee model using the ultra-low-dose computed tomography (CT) scan for preoperative planning and simulated surgery. Methods Thirty-six patients were divided into the standard-dose protocol group (A) and ultra-low-dose protocol group (B). The anteroposterior diameter, left and right diameter of femur, anteroposterior diameter of tibial plateau (APTP), left and right diameter, distance from the intercondylar ridge to tibial tuberosity, lower femur angle, and upper tibial angle were measured on CT images. On the 3D printed knee joint model, Vernier calipers were used to measure: anteroposterior diameter, left and right diameter of the internal and external condyles of femur; left and right diameters, anteroposterior diameters of tibial plateau; upper and lower meridian, left and right diameters of patella. Results With group A as reference, the effective radiation dose in group B was significantly reduced to 97.0% (36.4 ± 3.7 uSv and 1.1 ± 0.2 uSv, respectively). There was no difference in objective parameters for 3DP model (p = 0.31–0.84). None of the quantitative parameters of image quality showed significant difference (p = 0.11–0.96). Despite lower score of image quality and 3DP model in group B (3.0 ± 0.0 vs. 2.1 ± 0.2, 2.9 ± 0.3 vs. 2.2 ± 0.4; p < 0.05), the diagnostic performance was consistent in the two groups (all scores ≥ 2). Image quality and 3DP printed models were highly consistent (k = 0.97). Conclusions Ultra-low-dose protocol reduces the radiation dose while maintaining the image quality of knee. It meets the requirement for 3DP model, internal fixation model selection, and simulated surgery.